Serum‐based miRNAs in the prediction and detection of recurrence in melanoma patients. Issue 1 (25th August 2014) - Fleming, Nathaniel H.; Zhong, Judy; da Silva, Inês Pires; Vega‐Saenz de Miera, Eleazar; Brady, Bobbi; Han, Sung Won; Hanniford, Doug; Wang, Jinhua; Shapiro, Richard L.; Hernando, Eva; Osman, Iman
<x xml:space="preserve">Abstract</x> BACKGROUND Identification of primary melanoma patients at the highest risk of recurrence remains a critical challenge, and monitoring for recurrent disease is limited to costly imaging studies. We recently reported our array‐based discovery of prognostic serum miRNAs in melanoma. In the current study, we examined the clinical utility of these serum‐based miRNAs for prognosis as well as detection of melanoma recurrence. METHODS Serum levels of 12 miRNAs were tested using qRT‐PCR at diagnosis in 283 melanoma patients (training cohort, n = 201; independent validation, n = 82; median follow‐up, 68.8 months). A refined miRNA signature was chosen and evaluated. We also tested the potential clinical utility of the miRNAs in early detection and monitoring of recurrence using multiple longitudinal samples (pre‐ and postrecurrence) in a subset of 82 patients (n = 225). In addition, we integrated our miRNA signature with publicly available Cancer Genome Atlas data to examine the relevance of these miRNAs to melanoma biology. RESULTS Four miRNAs (miR‐150, miR‐30d, miR‐15b, and miR‐425) in combination with stage separated patients by recurrence‐free survival (RFS) and overall survival (OS) and improved prediction of recurrence over stage alone in both the training and validation cohorts (training RFS and OS, P < .001; validation RFS, P < .001; OS, P = .005). Serum miR‐15b levels significantly increased over time in recurrent patients (P < .001), adjusting for endogenous controls as well as age, sex, and initial stage. In nonrecurrent patients, miR‐15b levels were not significantly changed with time (P =.17). CONCLUSIONS Data demonstrate that serum miRNAs can improve melanoma patient stratification over stage and support further testing of miR‐15b to guide patient surveillance. Cancer 2015;121:51–59. © 2014 American Cancer Society.